2004
DOI: 10.4049/jimmunol.173.9.5644
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Presentation of Listeria-Derived CD8 T Cell Epitopes Requires Unstable Bacterial Translation Products

Abstract: Presentation of bacteria-derived CD8 T cell epitopes by dendritic cells (DC) requires either their direct infection or that DC acquire and cross-present Ags from other infected cells. We found that cross-presentation of Listeria monocytogenes-derived CD8 T cell epitopes was much stronger than direct Ag presentation by infected murine DC. Cross-presentation of Listeria-derived CD8 T cell epitopes showed unique physiological requirements. It was dependent upon the delivery of unstable bacterial translation produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Thus from model III it can be predicted that after Ag uptake by external loading or by cross-presentation antigenic peptides will be presented most efficiently if they are rapidly degraded and yield stable peptide/MHC complexes. Interestingly, this prediction is in line with the observation that the cross-presentation of L. monocytogenes-derived antigenic peptides requires the uptake by DC of a instable but not finally processed Ag from infected cells (Janda et al, 2004). As can be inferred from Eq.…”
Section: Article In Presssupporting
confidence: 64%
“…Thus from model III it can be predicted that after Ag uptake by external loading or by cross-presentation antigenic peptides will be presented most efficiently if they are rapidly degraded and yield stable peptide/MHC complexes. Interestingly, this prediction is in line with the observation that the cross-presentation of L. monocytogenes-derived antigenic peptides requires the uptake by DC of a instable but not finally processed Ag from infected cells (Janda et al, 2004). As can be inferred from Eq.…”
Section: Article In Presssupporting
confidence: 64%
“…Besides, a role for HSP in cross-presentation was either not addressed or indirectly looked at (20 -23, 49), while others have reported that LCMV-NP does not access the cross-priming pathway (19). Of a particular interest is the data reported by Janda et al (49) examining secreted bacterial proteins with a half-life of 90 min in ADCs (49) and reporting, in contrast to our findings, that unstable bacterial translation products were more efficient than mature proteins as an antigenic source for cross-presentation. In this system, the proteins examined for crosspresentation were synthesized in the bacterium before being secreted in the cytosol of infected cells.…”
Section: Discussionmentioning
confidence: 78%
“…To evaluate the ability of PLAP to generate 9mer model antigenic peptides from 10mer precursors we analyzed the trimming of 7 model 10mer peptides, 5 of which correspond to naturally occurring antigenic peptide precursors. Three of the peptides we tested (sequences IRLRPGGKKK, KSLYNTVATL and KGYKDGNEYI) correspond to natural precursors of epitopes found to be cross-presented (34, 35). Figure 3 demonstrates characteristic chromatograms from trimming reactions highlighting accumulated products.…”
Section: Resultsmentioning
confidence: 99%